Studi Fenomenologi Peran Perempuan Dalam Rumah Tangga, Wirausaha, dan Peningkatan Ekonomi Keluarga di Wilayah Pesisir Utara Semarang - Dyah Setyoningrum, Ari Ani; Nindita, Kirtyana (Jurnal Maritim Polimarin, 2024)
Entrepreneurial women are an interesting phenomenon because they are considered a second class group after men. However, women have a unique set of skills that men do not have that can be utilized in entrepreneurship. In this era, has shifted the role of women, especially from domestic role to public role. The economic contribution of women cannot be underestimated. This study uses a qualitative approach. Data collection were carried out by interviews, questionnaires and observation. The purpose of this study is to prove the role of women in the household, the role in entrepreneurship and the family economy. The role of women in the household is still placed as the main person in charge of family activities. The role of women in entrepreneurship places women as the main actors and able to develop their business. Women have the opportunity to generate income and reduce the economic limitations of their families